The effect of COVID vaccination timing on the seroprevalence of IgG antibodies: evidence from the Guayas region of Ecuador - Malacatus-Arboleda, Aurora; Barbotó-Ramírez, Erick; Sánchez, Gonzalo E.; Moscoso, Bernard; Rhodes, Lauren A.; Coloma, Josefina; Guevara, Ángel; Espinoza-Fuentes, Fernando; Fernández-Cadena, Juan Carlos; Morey-León, Gabriel; Andrade-Molina, Derly (Frontiers in Public Health, 2025)
Background and aimsTimely distribution of COVID-19 vaccines was particularly important for developing countries that do not have strong health systems and related infrastructure. We analyze data from the Guayas province of Ecuador, an area particularly affected by the pandemic, to determine the seroprevalence of SARS-CoV-2 and the effect of the timing of the second dose of COVID-19 vaccines on the seroprevalence SARS-CoV-2 IgG antibodies.MethodsThis cross-sectional study involved 1,761 individuals aged 18 and older who voluntarily enrolled prior to and during the initial phase of vaccine rollout in Ecuador (October 2020 to July 2022). IgG anti-SARS-CoV-2 RBD antibodies were assessed by an in-house ELISA to evaluate the immune response to Pfizer (BioNTech, Spike mRNA) and AstraZeneca (Oxford, AstraZeneca Spike) vaccine in the Guayas province. Ordinary least squares (OLS) regressions were employed to determine the effect of delayed second doses later than prescribed by the manufacturer for both vaccines.ResultsBefore the vaccination campaign, we estimated an RBD IgG seroprevalence of 27.7% (95% CI: 23.6–27, n = 469). The estimate increased to 89.4% (95% CI: 87.7–91.18, n = 1,235) after the first vaccine dose and to 92.6% (95% CI: 90.7–94.5, n = 748) after the second dose. Individuals who received the second dose of the Pfizer vaccine later than the recommended dose showed significantly lower levels of IgG antibodies 2–3 weeks after receiving the second dose than those who received the dose within the recommended timeframe. Furthermore, we did not find any effect on RBD IgG antibody levels in those who received a second dose of the AstraZeneca vaccine during the first and second parts of the recommended vaccination window.ConclusionThe results suggest that a significant portion of the study population was already infected with SARS-CoV-2 prior to the vaccination. As expected, seropositivity increased alongside vaccination efforts. We determined that Pfizer vaccine recipients should be adhered to vaccine timing guidelines. Furthermore, resource-limited countries should consider administering vaccines with flexibility in dosing intervals, such as AstraZeneca, as it allows for a wider time frame without significantly reducing the boosting of IgG antibodies.